Pedagogies and Literacies, Disentangling the Historical Threads: An Interview with Bill Cope and Mary Kalantzis. Issue 1 (2nd January 2018) - Cope, Bill; Kalantzis, Mary; Smith, Anna
ABSTRACT: In this discussion with educational researchers and New London Group conveners, Bill Cope and Mary Kalantzis, we discuss the origins, life, and future of the New London Group's multiliteracies framework. We reflect on the initial goals the group had over 20 years ago for more equitable schooling opportunities, and what is yet to be done to reach these ideals. We consider how Cope and Kalantzis' work in schools since that time, and in the literacy field more generally, has been informed by multiliteracies, specifically how issues of equity, consequences of traditional views of language and literacy, and advancing technologies continue to necessitate shifts in educational policy and practice that will allow for teachers to engage in flexible, responsive, and transformative teaching.